Model Gereja yang Berorientasi pada Tujuan: Prinsip-Prinsip Transformasi Gereja dalam Konteks Modern - Agra Pahala Prima Lumbantungkup; Aprianus Moimau (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
This article discusses the purpose-oriented church model as a relevant strategy in facing the challenges and dynamics of the church in the modern era. In the context of globalization, secularism, and rapid social change, many churches face an identity crisis and declining congregational engagement. The purpose-oriented model offers a systematic approach to strengthening the church's mission through a clear vision, effective strategy formulation, and active congregational participation. The research method used in this study is an in-depth literature analysis, covering various sources such as scriptures, contemporary theological books, and scholarly articles related to church transformation. In addition, this study evaluates several case studies of churches that have successfully implemented this model to better reach and serve their communities. The results of the study indicate that churches that apply the principles of the purpose-oriented model are not only able to increase congregational engagement but can also adapt better to the needs of the ever-evolving community. Thus, this article becomes a reference source for church leaders and academics in designing effective strategies for church transformation and growth in the future.